Staying afloat in the milk business: Borrowing and selling on credit among informal milk vendors in Nairobi - Myers, Emily; Heckert, Jessica; Galiè, Alessandra; Njiru, Nelly; Alonso, Silvia (International Food Policy Research Institute, 2021)
Studies on credit schemes for small-scale entrepreneurs have documented their potential to alleviate poverty and improve food security, nutrition, and health outcomes in low- and middle-income countries. Other studies find mixed impacts of credit schemes on reducing income inequality, empowering women, and enhancing children’s education. Moreover, growing evidence finds that entrepreneurs offer credit to customers; little is known about what this practice means for entrepreneurs, and even less about gendered differences in this practice. Herein, we consider the case of final retailers in agricultural value chains and examine how male and female informal milk vendors from peri-urban Nairobi borrow and sell on credit, and how these experiences affect their businesses where there are few formal safeguards to ensure repayment. In 2017, we conducted 49 individual interviews, four key informant interviews, and six focus groups with men and women who were current or former milk vendors. A thematic analysis revealed that vendors sell on credit to appeal to customers, which may be advantageous when vendors need to rid themselves of milk before it spoils, regardless of gender. With few strategies to recoup costs from customers who fail to repay, however, failure to collect debt may cause default for vendors who acquired milk via informal borrowing. The consequences are likely more severe for women vendors, who generally have less capital to fall back on relative to men. Development organizations should identify gender-sensitive financial services that can help entrepreneurs maintain viable businesses despite the volatility of borrowing and selling on credit.